Biomechanical analysis equipment supply in tennis using the latest optic electronic movement recording - Гамалій, В. В.; Литвиненко, Ю. В. (Slobozhanskyi Herald of Science and Sport, 2011)
The article presents quantitative and qualitative analysis of the characteristics of equipment of motor actions in the performance of skilled tennis players in the filing. Data obtained with the help of modern optic electronic systems for registration and motion analysis, allow in-depth study of the essence of the mechanisms of construction and realization of these movements in terms of competitive activity.